Statistical inference for a stochastic generalized logistic differential equation - Baltazar-Larios, Fernando; Delgado-Vences, Francisco; Diaz-Infante, Saul; Gomez, Eduardo Lince (Communications in nonlinear science & numerical simulation, 2024)
In this research we aim to estimate three parameters in a stochastic generalized logistic differential equation. We assume the intrinsic growth rate and shape parameters are constant but unknown. To estimate these two parameters, we use the maximum likelihood method and establish that the estimators for these two parameters are strongly consistent. We estimate the diffusion parameter by using the quadratic variation processes. To test our results, we evaluate two data scenarios, complete and incomplete, with fixed values assigned to the three parameters. In the incomplete data scenario, we apply an Expectation Maximization algorithm. •MLE for three parameters in a stochastic generalized logistic differential equation.•The growth rate and shape are estimated using ML and they are shown to be consistent.•The ML estimator proposed exhibits a high level of efficiency and robustness.